Combining Fluorescent Cell Sorting and Single B Cell Amplification to Screen the Monoclonal Antibody Gene against Human Glypican-1 in Pancreatic Cancer. (6th September 2021) - Huang, Mi; Ma, Yingying; Gao, Xiaoyan; Li, Xinyang; Ding, Quan; Liu, Chuxin; Liu, Xiaopan; Zhang, Hang; Yang, Naibo
Abstract : In this report, one novel method has been developed to screen the monoclonal antibody against human pancreatic cancer biomarker glypican-1 (GPC1) through the combination of fluorescent cell sorting and single B cell amplification. GPC1-positive B cells were sorted out from the peripheral blood mononuclear cells (PBMCs) by fluorescent cell sorting after the GPC1 immunization to the New Zealand white rabbit. Then, total RNA was extracted and reversely transcribed into cDNA, which was used as the template, and the variable region sequences of both heavy and light chains were amplified from the same B cell. Next, their recombinant antibody was expressed and purified from the human 293T cell after the antibody gene amplification and expression vector construction. The enzyme-linked immunosorbent assay (ELISA) and flow cytometry assays were used to determine the antibody affinity. The antibody named GPC-12 that we screened and obtained was proven to have natural heavy-light chain pairing information, and it was highly specific to the GPC1 antigen, and the affinity could reach 1 × 10 −7  M. Overall, an effective and novel method has been successfully developed to screen the antibody by combining the fluorescent cell sorting and single-cell amplifying technologies, which was proved to be workable in our setting.